Studi Kasus Pencegahan Medication Error Melalui Penerapan SOP Sentralisasi Obat - muwa, maria anjelina; Meo, Maria Yulita (Jurnal Ilmiah Wahana Pendidikan, 2024)
Centralization of medicines is an effort to prevent medication errors and improve patient safety in hospitals. The aim of this case study is to explain how to prevent medication errors through implementing centralized drug SOPs in the Dahlia Room BLUD RSUD dr. T.C. Hillers Maumere. Research method: using descriptive methods with a case study approach. The results of the SWOT analysis show that the implementation of drug centralization in the Dahlia Room at Dr. Tc. Hillers Maumere Regional Hospital obtained an IFAS value of -1, while the EFAS value was 0.4. The mapping results in the Flyover Diagram show that the implementation of drug centralization is in the WO quadrant, so the strategic steps that need to be taken are progressive, which means that the internal weaknesses of the Dahlia Room at RSUD BLUD Dr.Tc.Hillers Maumere need to be improved to get more external opportunities.